Circulation of canine parvovirus among dogs living in human-wildlife interface in the Atlantic forest biome, Brazil. Issue 12 (December 2017) - Vieira, Flávia V.; Hoffmann, Daniel J.; Fabri, Carolina U.F.; Bresciani, Katia D.S.; Gameiro, Roberto; Flores, Eduardo F.; Cardoso, Tereza C.
Abstract: Despite of the role of domestic dogs as reservoirs for threatening viral diseases for wild carnivores, few studies have focused to identify circulation of viruses among dogs living in human/wildlife interfaces. To identify canine parvovirus (CPV) types circulating in dogs living in an Atlantic forest biome, faecal samples (n = 100) were collected at the same period (one week) corresponding to each of four areas, during 2014 to 2016 and corresponded to 100 different individuals. CPV was isolated in cell culture from 67 out 100 (67%) samples from healthy dogs. Cytopathic effects were characterized by total or partial cell culture lysis. Genome sequences of CPV-2a (10%), CPV-2b (7%) and CPV-2c (50%) were concomitantly detected by PCR and nucleotide sequencing. The current study addresses the importance of monitoring CPV circulation among dogs presenting potential contact with wildlife species.